KENDARAAN OTONOM DI LAUT CHINA SELATAN: MASA DEPAN KEAMANAN MARITIM INDONESIA - Permatasari, Harnung Indah; Risdhianto, Agung; Almubaroq, Hikmat Zakky (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The conflict in the South China Sea continues to be a crucial issue triggered by overlapping territorial claims and its wealth of natural resources, making it the centre of geopolitical attention. For Indonesia, as the largest archipelagic state, maintaining maritime security, especially in Natuna waters, is a top priority. Despite increased military efforts, challenges such as illegal fishing, territorial violations and limited naval resources remain. This article explores the potential of Autonomous Vehicles (AV) technology-including Autonomous Underwater Vehicles (AUV), Unmanned Aerial Vehicles (UAV), and Unmanned Combat Aerial Vehicles (UCAV)-as a transformative solution to enhance maritime security. Through a qualitative descriptive approach, this research highlights how AVs can optimise border surveillance, ensure continuous monitoring, and reduce operational risks for personnel. The article also discusses the importance of international collaboration and technology transfer to develop AV capabilities for Indonesia's maritime defence. By combining advanced technology and strategic diplomacy, Indonesia can strengthen its sovereignty while contributing to regional stability in the South China Sea